Effects of Immunosuppressants on Immune Response to Vaccine in Inflammatory Bowel Disease - Cao, Yuan (Chin Med J (Engl), 2015)
OBJECTIVE: To evaluate the response rate to vaccination in different treatment groups (nonimmunosuppressants and immunosuppressants). DATA SOURCES: We completed an online systematic search using PubMed to identify all articles published in English between January 1990 and December 2013 assessing the effect of the response rate to vaccination in different treatment groups (with and without immunomodulators). The following terms were used: “inflammatory bowel disease (IBD)” OR “Crohn's disease” OR “ulcerative colitis” AND (“vaccination” OR “vaccine”) AND (“corticosteroids” OR “mercaptopurine” OR “azathioprine” OR “methotrexate [MTX]”) AND “immunomodulators.” STUDY SELECTION: The inclusion criteria of articles were that the studies: (1) Randomized controlled trials which included patients with a diagnosis of IBD (established by standard clinical, radiographic, endoscopic, and histologic criteria); (2) exposed patients received immunomodulators for maintenance (weight-appropriate doses of 6-mercaptopurine/azathioprine or within 3 months of stopping, 15 mg or more MTX per week or within 3 months of stopping; (3) exposed patients received nonimmunomodulators (no therapy, antibiotics only, mesalazine only, biological agent only such as infliximab, adalimumab, certolizumab or natalizumab or within 3 months of stopping one of these agents). The exclusion criteria of articles were that the studies: (1) History of hepatitis B virus (HBV), influenza or streptococcus pneumoniae infection; (2) patients who had previously been vaccinated against HBV, influenza or streptococcus pneumoniae; (3) any medical condition known to cause immunosuppression (e.g. chronic renal failure and human immunodeficiency virus infection); (4) individuals with positive hepatitis markers or liver cirrhosis; (5) patients with a known allergy to eggs or other components of the vaccines and (6) pregnancy. RESULTS: Patients treated with immunomodulators were associated with lower response rates to vaccination. CONCLUSIONS: Immunomodulators may impair the immune response to vaccination in patients with IBD. Vaccination should be made at the time of diagnosis or before starting immunosuppressed therapy.